2019
DOI: 10.1101/gr.248922.119
|View full text |Cite
|
Sign up to set email alerts
|

LTR retroelement expansion of the human cancer transcriptome and immunopeptidome revealed by de novo transcript assembly

Abstract: Dysregulated endogenous retroelements (EREs) are increasingly implicated in the initiation, progression, and immune surveillance of human cancer. However, incomplete knowledge of ERE activity limits mechanistic studies. By using pan-cancer de novo transcript assembly, we uncover the extent and complexity of ERE transcription. The current assembly doubled the number of previously annotated transcripts overlapping with long-terminal repeat (LTR) elements, several thousand of which were expressed specifically in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(118 citation statements)
references
References 57 publications
7
105
0
Order By: Relevance
“…In nine out of the twelve types of cancers, the overall expression levels of HERVs were increased compared to that in the adjacent normal tissues ( Fig. 1B ), consistent with previous reports 2024 . Dimension reduction analysis based on HERV expression profiles showed that each type of cancer displays a distinguishable pattern of HERV expression ( Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In nine out of the twelve types of cancers, the overall expression levels of HERVs were increased compared to that in the adjacent normal tissues ( Fig. 1B ), consistent with previous reports 2024 . Dimension reduction analysis based on HERV expression profiles showed that each type of cancer displays a distinguishable pattern of HERV expression ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…The expression of HERVs in normal tissues is controlled by epigenetic mechanisms such as DNA methylation and repressive histone modifications 18,19 ; in contrast, HERV expression is highly elevated in various types of cancers 2024 . Since the elevation of HERV expression in tumors is presumably caused by epigenetic reactivation, the expressed HERVs could upregulate the expression of adjacent genes.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent de novo cancer transcriptome assembly (Attig et al, 2019) identified a chimeric transcript between annotated exons of ACE2 and an LTR16A1 retroelement, integrated in intron 9 of the ACE2 locus. This transcript, which we refer to here as LTR16A1-ACE2, is initiated at the LTR16A1 retroelement, which functions as a cryptic promoter and includes exons 10-19 of ACE2 ( Figure 1A).…”
Section: Ltr16a1-ace2 Is a Tissue-specific Novel Isoform Of Ace2mentioning
confidence: 99%
“…Transcripts were previously assembled on a subset of the RNAseq data from The Cancer Genome Atlas (TCGA) (Attig et al, 2019). The alternative promoter within ACE2 was more highly expressed in lung squamous carcinomas than the canonical isoform, prompting us to investigate its biology.…”
Section: Transcript Identification and Read Mappingmentioning
confidence: 99%
See 1 more Smart Citation